Differential Analysis of Fecal SCFAs and Their Contribution to Adipogenesis in UCP1 Knock-In Pigs - Chengyu Zhao; Jianfei Pan; Yanfang Wang; Jianguo Zhao; Jiaojiao Huang (Veterinary Sciences)
This study aimed to investigate the changes in fecal short-chain fatty acids (SCFAs) content in UCP1 knock-in pigs (KI pigs) and their effect on adipogenesis. Fecal samples from five 6-month-old wild-type (WT) and KI pigs were collected for targeted metabolomics and 16s rRNA sequencing analyses to identify differences in SCFAs and gut microbiota that may contribute to regulating fat deposition in pigs. The metabolome of pig fecal samples targeted for an analysis of SCFAs identified seven SCFAs, with caproic acid (except isovaleric acid) being the significantly different one. The results of the fecal 16s rRNA analysis demonstrated a notable reduction in the abundance of Streptococcus spp. in the KI pigs in comparison to the WT pigs, with a statistically significant difference. Correlation analyses demonstrated a statistically significant positive correlation between the abundance of Streptococcus spp. and SCFAs, as well as pig body weight and fatness. It was postulated that the reduction in SCFAs in the intestinal tracts of KI pigs may be associated with a reduction in Streptococcus spp. abundance. Compared to WT pigs, the concentration of fecal SCFAs in KI pigs was significantly reduced, which may be related to the decreased abundance of Streptococcus. The in vitro experiments showed that caproic acid could significantly enhance the differentiation efficiency of porcine SVF cells into mature adipocytes by activating the FFAR4 gene.